CARDIORENAL SYNDROME: NARRATIVE REVIEW - Laksono, Sidhi; Nugraha, Dhiki (Journal Medical Universitas muhammadiyah Makassar, 2023)
Cardiorenal syndrome is a disorder that involves the heart and kidneys, acute or chronic dysfunction of one organ can induce acute or chronic dysfunction of other organs. Renal dysfunction associated with acute heart failure, and vice versa, causes considerable morbidity and mortality. Until recently, there has been no consistent and effective strategy in the management of patients with cardiorenal syndrome. Generally, only done by reducing the volume of fluid so as not to worsen kidney function. Early identification leads to more effective treatment and shorter hospitalization. A multidisciplinary approach involving cardiologists and renal specialists is essential.